Tradition and Social Value of Drinking Coffee - Bahagia Bahagia; Rimun Wibowo; Muhammad Rifay; Siti Pauziah; Tika Kartika (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
Drinking coffee is a tradition and social value. This study aims to find the cultural values and traditions of drinking coffee in Acehnese society, precisely in Takengon. Another goal is to find out the social, economic values and changes in coffee drinking. The research method used is a qualitative research method. The research sample was taken using a purposive method. The results of the study indicate that there are socio-cultural changes in Indonesia, one of which is the tradition of drinking coffee, precisely in Central Aceh district, Takengon. If in the past, most people drank coffee in ordinary coffee shops at affordable prices, now coffee shops are designed more modern with attractively packaged marketing so that many customers are interested. Another finding is that there are social values such as the value of friendship, the value of brotherhood and social relations with fellow friends when drinking coffee. There are even values of conversation about social life in coffee shops. Another finding is that there are livelihood values because coffee shops will generate livelihoods for coffee shop owners and coffee producers. Finally, there are ethical values that must be used especially to produce quality coffee